Caravaggio : the artist and his work - Ebert-Schifferer, Sybille (J. Paul Getty Museum, 2012)
"The book examines Caravaggio's paintings within the context of 16th century Italian mores. It shows that his unparalleled intermingling of the profane and the sacred was meant to stimulate emotion, amaze the cognoscenti, and lead people to faith"--